Situation and problems in domestic and foreign policy: consideration of the Report of the Presidency of the SFRY in the Assembly of Yugoslavia (Jugoslovenski pregled, Newspaper Pub.House: H,Belgrade Serbia, 1984)
This book contains the seventh joint session of the Federal Chamber and Chamber of Republic and provinces, held on 19 April 1984. Before being considered at the joint session, the Report of the Presidency of the SFRY was the subject of wide-range discussion in the working bodies of the chambers of the assembly of the SFRY.
Includes bibliographical footnotes.
hza 03/07/2018
Loans
Keywords: Foreign affairs; Yugoslavia